Sticky card for Empoasca onukii with bicolor patterns captures less beneficial arthropods in tea gardens. (November 2021) - Bian, Lei; Cai, Xiao-Ming; Luo, Zong-Xiu; Li, Zhao-Qun; Chen, Zong-Mao
Abstract: Color sticky cards are extensively used to trap or monitor pests. One obvious disadvantage of color sticky cards is that a lot of non-target insects are also trapped. To ameliorate this problem, we investigated the influence of different components of color sticky cards in tea gardens. Specifically, we examined the effects of substrate pattern design, glue thickness, and auxiliary volatiles on the number of captured target pests, Empoasca onukii, a serious pest of tea plants, and major beneficial arthropods. Field results showed that some colors were repellent to beneficial arthropods. Therefore, we designed a bicolor pattern that combined an attractive color (gold, RGB: 255, 215, 0) with a repellent color (red, RGB: 255, 0, 0) to significantly decrease the number of beneficial arthropods captured on color sticky cards without affecting the number of captured target pests. The pattern shape had no impact on effectiveness, but more target pests and beneficial arthropods were captured when the proportion of the attractive color or the glue thickness increased. A suitable attractive color proportion (50 %) and glue thickness (0.4 mm) can help reduce the number of captured beneficial arthropods. As an auxiliary measure, the effect of volatile compounds was significant but complicated, and satisfactory volatiles were difficult to identify. The effectiveness of a bicolor pattern design would vary by target pest and community composition. Nevertheless, this method could become an important component of pest trapping if color traps are redesigned to reduce unintended impacts on beneficial arthropods. Highlights: Some colors were repellent to beneficial arthropods in tea gardens Sticky card with bicolor pattern captures less beneficial arthropods Suitable glue thickness can reduce the captures of beneficial arthropods Captures of insect species on the sticky card could be influenced by volatiles